Research progress on nutritional support for patients with liver cirrhosis complicated by upper gastrointestinal bleeding - Dong, Yun; Chen, Pei-Yue; You, Chuan; Li, Jing-Dong; Chen, Song-Tao (Frontiers in Nutrition, 2025)
Upper gastrointestinal bleeding (UGIB) in patients with liver cirrhosis represents a common clinical emergency characterized by sudden onset and high mortality. The prognosis of these patients is strongly correlated with their nutritional status. Malnutrition serves as a key determinant of clinical outcomes, making nutritional support a critical component of comprehensive care. Early identification and timely intervention can effectively prevent disease progression, reduce complication rates, and improve both treatment efficacy and survival. This article synthesizes evidence from previous research to summarize nutritional support strategies for cirrhotic patients with upper gastrointestinal bleeding(UGIB). It addresses nutritional screening tools, routes of administration, and fundamental principles of nutritional support, with the aim of offering a reference for clinical management.